2018
DOI: 10.1177/0010414018758760
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Colonial Rule Undermines Support for Democracy: Evidence From a Natural Experiment in Namibia

Abstract: This article identifies indirect and direct colonial rule as causal factors in shaping support for democracy by exploiting a within-country natural experiment in Namibia. Throughout the colonial era, northern Namibia was indirectly ruled through a system of appointed indigenous traditional elites whereas colonial authorities directly ruled southern Namibia. This variation originally stems from where the progressive extension of direct German control was stopped after a rinderpest epidemic in the 1890s, and, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…While this study does not exploit some quasi-random variation on chief's competition, it is important as it shows with a phenomenal dataset that traces the chieftaincy for over a century the continuity of de facto political rule and the persistence of rural institutions. Lechler and McNamee (2018) look at Namibia, an interesting case because the North was ruled via local chiefs, while the German and South African administration ruled directly the Southern provinces.…”
Section: Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…While this study does not exploit some quasi-random variation on chief's competition, it is important as it shows with a phenomenal dataset that traces the chieftaincy for over a century the continuity of de facto political rule and the persistence of rural institutions. Lechler and McNamee (2018) look at Namibia, an interesting case because the North was ruled via local chiefs, while the German and South African administration ruled directly the Southern provinces.…”
Section: Evidencementioning
confidence: 99%
“…Soon afterwards the colonial administration put a veterinary cordon fence and in 1907 it institutionalized a formal police boundary separating "white" and "black" West-South Africa. Lechler and McNamee (2018) compare political beliefs and participation using Afrobarometer Surveys on the two sides of the colonial border. The regression discontinuity estimates uncover sharp differences at the border; pro-democracy beliefs and electoral participation are considerably lower on the Northern side of the colonial border that was ruled indirectly via despotic chiefs.…”
Section: Evidencementioning
confidence: 99%
“…Other scholars contend that indirect rule, a practice typically associated with British colonialism, engendered distinctively antidemocratic tendencies. That is, pro-autocratic political ideologies were more likely to persist in areas where colonial magistrates delegated local authority to traditional leaders (Lechler & McNamee, 2018; Mamdani, 1996). Yet, it is unlikely that colonial-era norms took root in a uniform, easily predictable fashion: disparate factors impacted the rate and magnitude of transmission.…”
Section: Early Statehood and Autocratic Socializationmentioning
confidence: 99%
“…Second, our work speaks to extant scholarship on long-run norm transmission (Becker et al, 2016; Chaudhary & Shrivastava, 2018; De Juan, 2017; Nunn & Wantchekon, 2011; Pop-Eleches & Tucker, 2020; Schulz et al, 2019) by showing that similarly to pre-industrial political institutions (Becker et al, 2016; Chaudhary & Shrivastava, 2018) and disruptive historical events (Besley & Reynal-Querol, 2014; Nunn & Wantchekon, 2011; Schulz et al, 2019), the enculturation efforts of precolonial political elites can be an enduring source of prevailing norms. We build upon the work of Lechler and McNamee (2018) who show in the context of Namibia that greater influence of traditional leaders in indirectly ruled areas continues to socialize individuals to accept nondemocratic sources of authority. Specifically, we show that the empirical regularities these authors identified in a single case generalize to other African countries.…”
Section: Introductionmentioning
confidence: 99%
“…During colonialism, these differences were fortified with the erection of the veterinary cordon fence (for a detailed historical account, cf. Lechler and McNamee, 2018). Still today, the northern traditional institutions are stronger and more hierarchically organized (cf.…”
Section: Namibia As a Paradigmatic Case Of Resurgencementioning
confidence: 99%